Evaluation of Digestability and Rumen Parameters Through In-vitro Concentrate Containing Binahong Flour as Secondary Compound - A. A. Widu; F. U. Datta; M. M. Kleden (Universitas Bengkulu, 2021)
This study was conducted to determine the effect of different levels of binahong flour used in concentrate feed on dry matter digestibility (DMD), organic matter digestibility (OMD), VFA and NH3 concentrations in vitro. The design used was a completely randomized design with 4 treatments and 4 replications. The treatments studied were: R0; concentrate feed without binahong flour, R1; concentrate feed contains 10% binahong flour, R2; concentrate feed containing 20% binahong flour, R3; concentrate feed contains 30% binahong flour. Based on the results of the study, the average DMD (%) R0 73.56±0.75, R1 74.50 ±0.61, R2 74.98±0.70, R3 76.65±0.90, OMD (%) R0 69.50±1.10, R1 69.82±1.00, R2 70.07±0.88, R3 72.61±0.99, VFA concentration (mM) R0 108.53±8.52, R1 110.75±6.51, R2 111.40±2.35, R3 112.77 ±14.76, NH3 concentration (mM) R0 9.74±0.74, R1 10.61±0.44, R2 11.55±0.41, R3 11.55±0.33. The results of statistical analysis confirmed that the treatment had a very significant effect on the increase in DMD, OMD, NH3 (P<0,01), but not significant on the total VFA concentration. The conclusion of this study is that the use of binahong flour up to a level of 30% in concentrate feed has an effect on increasing in DMD, OMD, VFA, and NH3 concentrations in vitro.